La formación inicial y continua de docentes de Matemáticas en Costa Rica - Alfaro Arce, Ana Lucía (2013)
The quality of education is related to the effectiveness of education provided by the teachers as well as to watch over the initial and ongoing training of teachers is essential to society because of the implications of this education on human development and consequently, on the country’s development. This report (paper) points out historical aspects of initial teacher training in Costa Rica, structures of the core content of initial training, ongoing training in mathematics education emphasizing recent actions, the role of research in education, technology and professional development in both elementary and high school education. It starts with a historical context followed by a section of strengths, weaknesses, threats, and key challenges that Costa Rica must face in pursuit of the quality of mathematics education.